The investigation of the luminescence properties of colloidal quantum dots based on cadmium chalcogenides - Mikhailov, I.I.; Tarasov, S.A.; Solomonov, A.V.; Matyushkin, L.B.; Mazing, D.S. (Functional Materials, 2014)
Samples of cadmium selenide colloidal quantum dots (CQDs) prepared in water and organic media were studied. The possibility to control luminescence peak position through technological parameters variation during synthesis process was shown and different luminescence mechanisms in CQDs were demonstrated. Cadmium selenide CQDs with inorganic shell of cadmium sulfide were synthesized and it allowed raising emission intensity several times.